(untitled) (Sociologisk Forskning, 1993)
Use of alcohol and psychotropics in Sweden This study of a representative Swedish sample of 5612 respondents from 1988, shows that the use of psychotropics in the general population is highly associated with bad health, as indicated by chronic diseases, especially the category of mental disorders. Also old age, the perception of bad health and various types of tiredness are strongly associated with the use of psychotropics. In general, the same pattern was found behind use of psychotropics as for other medicines in terms of sickness, perceived health, age, gender. Users of psychotropics also reported many contacts with the health care system. Altogether, the results argue for the interpretation, that psychotropics mainly are used in order to cope with bad health. This may also explain why more females than males use psychotropics. Contrary to psychotropics, alcohol use showed no association with bad health in general. If there are any functional similarities between alcohol and psychotropics, they are found between abstinence from alcohol and use of psychotropics. Also abstinence from alcohol seems to be connected with strategies to cope with health problems. Survey data in general and ours in particular have poor validity with regard to deviant behaviour. In order to study the combined use of alcohol and psychotropics, clinical populations have to be studied. Our data do not allow for any conclusion in this direction.